Economic Perspectives on Marketing Integration: Enhancing Purchasing Decisions through Online and Offline Strategies at Mancafe - Nazmah, Nazmah; Prihatin, Titis Budi; Dalimunthe, Muhammad Abror; Harianto, Bambang; Sani, Fajrin Hanif (Yayasan Riset dan Pengembangan Intelektual, 2025)
In the rapidly evolving digital era, the integration of online and offline marketing strategies has emerged as an effective approach to influencing consumer purchasing decisions. This study explores the implementation of these strategies by Mancafe, a coffee shop in Medan, and their impact on customer purchasing behavior. Using a qualitative case study approach, data were collected through interviews, observations, and document analysis. The findings reveal that online marketing through social media and e-commerce platforms significantly expands customer reach, while offline marketing, particularly through direct customer experiences, plays a crucial role in building trust and loyalty. The synergy of these strategies enhances brand awareness and customer retention. This study provides valuable insights for business owners on optimizing marketing strategies to strengthen competitiveness and improve customer satisfaction